Ising Superconductivity and Magnetism in NbSe_{2} - Darshana Wickramaratne; Sergii Khmelevskyi; Daniel F. Agterberg; I. I. Mazin (Physical Review X, 2020)
Recent studies on superconductivity in NbSe_{2} have demonstrated a large anisotropy in the superconducting critical field when the material is reduced to a single monolayer. Motivated by this recent discovery, we use density-functional theory (DFT) calculations to quantitatively address the superconducting properties of bulk and monolayer NbSe_{2}. We demonstrate that NbSe_{2} is close to a ferromagnetic instability, and analyze our results in the context of experimental measurements of the spin susceptibility in NbSe_{2}. We show how this magnetic instability, which is pronounced in a single monolayer, can enable sizable singlet-triplet mixing of the superconducting order parameter, contrary to contemporary considerations of the pairing symmetry in monolayer NbSe_{2}, and discuss approaches as to how this degree of mixing can be addressed quantitatively within our DFT framework. Our calculations also enable a quantitative description of the large anisotropy of the superconducting critical field, using DFT calculations of monolayer NbSe_{2} in the normal state.